The management whisperer: Ensuring organisational sustainability, viability and competitive advantage through management development via a practice based future fit talent pipeline - Harmse, Ingrid (Research of GSB, 2017)
The researcher was appointed into the position of General Manager within the Clothing and General Merchandise Supply Chain in a large retail organisation as part of a transformation strategy to turn around a business unit which had historically been delivering substandard performance and had led to significant impacts on organisational performance. Despite the organisation having a number of mechanisms in place to assist line managers to manage the life cycle of an employee during their employment, the performance measures as well as selection of a talent pipeline were measured against the framework of an underperforming environment. Competence was therefore benchmarked on overrated performance against underrated goals which led to ineffective performance and no validity in talent identification. Critical Realism was chosen as an ontological philosophy. Data was generated through four research cycles and processed through grounded theory meta-synthesis methodology. Four core variables emerged from the research: Identification of inherent DNA required for talent succession development, Quality of leadership, Effectiveness of a performance plan and Leading with heart. The driving variable within the balancing loop identified in the causal mechanism was Quality of leadership which is the initial point of influence in the system, and sets off a chain of cause and effect interactions between all the other variables, resulting in either a positive or negative stabilization within this system. This research suggests interventions and mechanisms to improve performance while simultaneously developing a future fit workforce who have the ability to focus on a number of moving parts at the same time. Efficiency is created through their competence in ensuring outstanding operational performance, the engagement and effective management of staff as well as the ability to handle constant change, complexity and uncertainty. The theory built, as well as the proposed interventions and mechanisms were tested and modified within the environment and delivered significant business results. The results achieved as a result of the implementation of the theory, are therefore concrete evidence of relevance, validity and utility. Contributions to practice, theory and research are discussed in this closing chapter of this dissertation.